Chinese herbal medicine Huangtu decoction in the treatment of acute upper gastrointestinal hemorrhage in a patient with chronic renal failure and related nursing measures (黄土汤治疗1例慢性肾功能衰竭患者急性上消化道出血的护理体会) - WANG Jiali (王佳丽); MA Xintong (马新童); WANG Yanyun (王艳云); BAI Donghai (白东海); WANG Yifei (王逸飞); KONG Lingxin (孔令新) (Association of Integrative Nursing, 2023)
This paper summarized the Chinese herbal medicine Huangtu decoction treatment and nursing management of acute upper gastrointestinal hemorrhage in a patient with chronic renal failure. The Chinese herbal medicine Huangtu decoction processed by special decocting method was administrated under the guidance of midnight-midday ebb flow. Comprehensive interventions including nutrition support, skin care, psychological care, prevention of anemia, exercise guidance and Traditional Chinese Medicine nursing techniques were carried out during the treatment, in order to relive the clinical symptoms of acute upper gastrointestinal hemorrhage and ensure patient safety and follow-up dialysis treatment (本文总结黄土汤治疗1例慢性肾功能衰竭患者急性上消化道出血的效果, 总结护理体会。运用特殊煎法个性化煎煮经方黄土汤加味并控制中药出汁量, 同时采用子午流注服药法, 以增强中药疗效。治疗期间加强患者饮食护理、心理护理、皮肤护理, 积极预防贫血, 进行运动指导, 实施耳穴压丸、穴位贴敷等中医护理技术, 旨在缓解临床症状, 帮助患者平稳过渡至持续性腹膜透析治疗。)